2007
DOI: 10.1177/1359105307080615
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Theory of Planned Behaviour Variables Mediate the Effects of Socio-demographic Variables on Homeless People's Participation in Service Programmes

Abstract: This article reports findings from two studies (N = 88, N = 100) using Ajzen's theory of planned behaviour (TPB) to predict homeless people's uptake of service programmes. Study 1 was conducted with an opportunity sample whereas Study 2 employed a representative sample. Both studies provide support for the application of the TPB, and demonstrate that the effects of demographic characteristics on behaviour were mediated by TPB variables. The discussion focuses on the role of attitudinal and normative components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…The results demonstrate that adolescents who perceived stricter perceived parental control had less intention and consumed less junk food. Our findings support the notion that perceived parental control directly and indirectly affects adolescents' intention to consume junk food Based on the findings of previous research (Christian et al, 2007;Courneya et al, 1999;Desrichard et al, 2007), we hypothesized that the distal variable (i.e., perceived parental control) would have an influence on adolescents' intention and behavior through the proximal variables. The results indicate that only PBC partially mediated the relation between perceived parental control and intention.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results demonstrate that adolescents who perceived stricter perceived parental control had less intention and consumed less junk food. Our findings support the notion that perceived parental control directly and indirectly affects adolescents' intention to consume junk food Based on the findings of previous research (Christian et al, 2007;Courneya et al, 1999;Desrichard et al, 2007), we hypothesized that the distal variable (i.e., perceived parental control) would have an influence on adolescents' intention and behavior through the proximal variables. The results indicate that only PBC partially mediated the relation between perceived parental control and intention.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, attention has been paid to the role of environment, social surroundings, and personality factors on health-related behaviors (de Bruijn, Kremers, Schaalma, van Mechelen, & Brug, 2005). In this context, several potential external or distal variables that may influence behavior have been proposed, such as sociodemographic variables (Christian, Armitage, & Abrams, 2007); age, gender, and locus of control (Armitage, Norman, & Conner, 2002); parental supervision (Desrichard et al, 2007); and personality (Courneya, Bobick, & Schinke, 1999). The TPB claims that the relation between distal factors such as environmental factors and behavior are mediated by the theory's social cognitive constructs (Ajzen, 1991).…”
mentioning
confidence: 99%
“…Self-efficacy—defined as perceived capability to perform a target behaviour (Bandura, 1977, 1986, 1997, 2004)—is a robust predictor of various health behaviours (Armitage & Conner, 2001; Godin & Kok, 1996), including physical activity (Bauman et al, 2012), healthy eating (AbuSabha & Achterberg, 1997), smoking cessation (Gwaltney, Metrik, Kahler, & Shiffman, 2009), alcohol abstinence (Adamson, Sellman, & Frampton, 2009), health behaviour change among cancer survivors (Park & Gaffey, 2007), and general health outcomes (Holden, 1991). Self-efficacy is the primary explanatory construct in Bandura’s (1986, 1997) social cognitive theory—one of the most often used health behaviour theories (HBTs) (Glanz & Bishop, 2010)—and is included in several other often-used HBTs, including protection motivation theory (Rogers, 1983), the health belief model (Rosenstock, Strecher, & Becker, 1988), and the transtheoretical model (Prochaska & DiClemente, 1983).…”
mentioning
confidence: 99%
“…In a more recent example of a TPB study examining homelessness, Christian, Armitage, and Abrams (2007) recruited 188 (mostly male) participants experiencing homelessness for two studies aimed at furthering investigations of the predictors underlying service utilization. The utility of the TPB was only partially supported as results of their Study 1 (based on an opportunity sample) found that attitude was the only standard TPB variable to predict intention.…”
Section: The Tpbmentioning
confidence: 99%